Localization of Elements Important for the Wound-Inducible Expression of a Chimeric Potato Proteinase Inhibitor II-CAT Gene in Transgenic Tobacco Plants. - Keil, M (1990)
The effect of progressive 5[prime] deletions within a potato proteinase inhibitor II promoter on wound-inducible expression of the chloramphenicol acetyltransferase (CAT) gene in leaves of transgenic tobacco plants was analyzed. After deletion of a region ranging from position -1300 to -700 with respect to the transcription start site, promoter activity was markedly reduced but still wound-inducible. Further deletion of approximately 200 base pairs resulted in a promoter activity that was below the detection limit, proving that the activity of the proteinase inhibitor II promoter is controlled by sequences upstream of position -514. Addition of the enhancer of the 35S promoter of the cauliflower mosaic virus (CaMV) either 5[prime] upstream or 3[prime] downstream of chimeric genes consisting of different proteinase inhibitor II promoter deletions (-700, -514, -210) fused to the CAT gene led to wound-inducible CAT gene expression in a fraction of transgenic plants containing either the "-700" or "-514" promoters, indicating the presence of wound-responsive elements in the promoter-proximal region. A fragment of the proteinase inhibitor II promoter comprising sequences between positions -1300 and -195 is able to confer wound-inducible expression to an inactive CaMV 35S promoter truncated at position -90 in either orientation, proving that this fragment displays wound-specific, enhancer-like properties. In addition, data are presented excluding that the proteinase inhibitor II 3[prime] end is of importance for wound-inducible gene expression.